Pemanfaatan Model Integratif dalam Meningkatkan Aktivitas Belajar Siswa untuk Pengembangan Kurikulum Merdeka - MS Viktor Purhanudin; Joni Hasperi; Wanda Oktaviani Putri; Suci Ramadhani; Muhammadong Muhammadong; Jetra Viktoria (Journal on Education, 2023)
Based on observations at SMP Negeri 7 Kerinci teachers in carrying out the learning process are menoton, fasif students, there is no interest in students to innovate so that learning is not effective. The integrative model is very important in the successful implementation of the independent curriculum. In addition, the low learning outcomes of students in learning and student learning activities need to be activated, this can be seen from the completeness of student learning which only reaches 40% and many students' scores are below KKM, for that it is very necessary to use better learning by using integrative models in learning. This research is a Classroom Action Research (PTK) consisting of Precycle, Cycle I, Silus II and Cycle III. Each cycle ends with an evaluation. Each cycle consists of planning, execution, evaluation and reflection. Based on the results of the research that has been carried out then analyzed the findings in the field so that it can be concluded that The use of integrative models in improving student learning activities for the development of an independent curriculum can increase the learning activities of SMP Negeri 7 Kerinci students.